2021
DOI: 10.1111/gove.12664
|View full text |Cite
|
Sign up to set email alerts
|

Within the shadow of hierarchy: The role of hierarchical interventions in environmental collaborative governance

Abstract: Existing literature often analyzes the effects of horizontal relationships on collaborative governance, though some scholars have started to recognize the role of hierarchical interventions. This paper identities two poorly examined areas of study. First, there is a lack of empirical studies to understand the diverse impacts of hierarchical interventions on collaborative governance. Second, there is little deliberation on how existing horizontal relationships can moderate the effects that hierarchical interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In addition, some research has already shown that a local government's air pollution collaboration network will also be affected by geographic relations, pollution issues, political systems, economic characteristics, and urban population size, etc. (Chen et al, 2019; Yang et al, 2022; Yi et al, 2018; Zhou & Dai, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some research has already shown that a local government's air pollution collaboration network will also be affected by geographic relations, pollution issues, political systems, economic characteristics, and urban population size, etc. (Chen et al, 2019; Yang et al, 2022; Yi et al, 2018; Zhou & Dai, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The Chinese central government's role in atmospheric protection is reflected in macro‐level policy planning and inter‐jurisdictional coordination. Higher level governments have the legitimacy and authority to impose regulations including coercive instruments on local collaborative governance (Chen et al, 2023; Zhou & Dai, 2022). Political evaluation tools, which are closely attached to political promotion, are also deployed by the central government to motivate local governments to achieve policy goals (Li & Zhou, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In China, influenced by top-down institutional arrangements, vertical intervention by the central government can change the incentive structure of local governments, thus promoting the coordination between central and local governments. Therefore, the vertical coordination between central and local governments under the hierarchical system is also an important embodiment of collaborative governance (Mu et al, 2019;Zhou and Dai, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For environmental governance, especially for haze governance, which is a complex cross-domain public affair, collaborative governance can reflect the complex dynamics and subject diversity of multi-level governmental collaborative haze governance. As a typical practice of central-local collaborative governance under China's hierarchical system, CEPI changes the incentive structure of local governments through top-down institutional arrangements, thus shaping the motivation of local governments to participate in the collaborative governance of haze (Mu et al, 2019;Zhou and Dai, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This question is examined through the theoretical lens of contested federalism, which argues that competing goals and incentives in state-local government relationships lead to policy misalignments that cause distinct political transaction costs, which can impede sustainability actions (Rabe 2011; Youm and Feiock 2019; Farmer 2021; Feiock 2008). This theoretical perspective suggests that multilevel governance support within these hierarchical relationships can reduce the vertically distributed transaction costs (Youm and Feiock 2019; Feiock 2009; Homsy and Warner 2015; Huang and Berry 2021; Zhau and Dai 2022). This hierarchical focus highlights how the differences in attributes across sustainability policy dimensions affect municipal decisions to engage in interjurisdictional collaboration.…”
Section: Introductionmentioning
confidence: 99%